Persepsi “Kafir” pada Muslim dan Non-Muslim: Konteks, Penggunaan, dan Komunikasi Partisipatif - Wahid, Abdul (Tuturlogi: Journal of Southeast Asian Communication, 2020)
The use of religious terms such as 'kafir' is seen as a form of radicalism because it discriminates against other groups; both Muslim and non-Muslim groups. Radicalism can encourage intolerant behavior and violence. In political contexts such as elections, mass groups often use these calls to discriminate against other groups that are considered to have different views. This study was conducted to find out how "kafir" are used and how participatory communication as a means of resistance. This study was conducted using a survey method for Muslim and non-Muslim students in Malang City. This study states, the context of "kafir" occurs in different ways. In social relations, kafir is used in a joke. But t is also considered tend to discrimination, especially when associated with conservative organizations and fundamentalist movements. When "kafir" are used discriminatively, respondents have the awareness to reject using the term. Forms of participatory communication are done through informal discussion forums rather than formal spaces.